2020
DOI: 10.1002/cbin.11365
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SNHG12 promotes vascular smooth muscle cell proliferation and migration via regulating miR‐199a‐5p/HIF‐1α

Abstract: The dysregulation of proliferation and migration of vascular smooth muscle cells (VSMCs) contributes to atherosclerosis (AS) and accumulating reports indicate the crucial role of long noncoding RNA in AS. However, the role of small nucleolar RNA host gene 12 (SNHG12) in regulating the phenotypes of VSMCs and AS remains largely unknown. Quantitative reverse‐transcription polymerase chain reaction (qRT‐PCR) was used to detect the expression levels of SNHG12 and miR‐199a‐5p in an in vivo AS model and VSMCs treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Second, whether miR‐199a‐5p contributes to AAA formation via regulation of VSMC senescence needs to be further verified in Ang II–infused Apoe ‐/‐ mice. Third, it has been reported that SHNG12 targeting miR‐199a‐5p/HIF‐1α contributed to atherosclerosis formation by mediating the phenotypes of VSMCs 42 . In addition to Sirt1, whether miR‐199a‐5p mediates VSMC senescence via regulation of other targets needs to be addressed in future study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Second, whether miR‐199a‐5p contributes to AAA formation via regulation of VSMC senescence needs to be further verified in Ang II–infused Apoe ‐/‐ mice. Third, it has been reported that SHNG12 targeting miR‐199a‐5p/HIF‐1α contributed to atherosclerosis formation by mediating the phenotypes of VSMCs 42 . In addition to Sirt1, whether miR‐199a‐5p mediates VSMC senescence via regulation of other targets needs to be addressed in future study.…”
Section: Discussionmentioning
confidence: 95%
“…Third, it has been reported that SHNG12 targeting miR‐199a‐5p/HIF‐1α contributed to atherosclerosis formation by mediating the phenotypes of VSMCs. 42 In addition to Sirt1, whether miR‐199a‐5p mediates VSMC senescence via regulation of other targets needs to be addressed in future study. Fourth, whether miR‐199a‐5p can injure other cell types including endothelial cells and fibroblasts to promote AAA formation has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…These data further confirmed the beneficial role of SNHG12 in the hypertensive vascular endothelial injury by targeting miR‐25‐3p. In addition, the research of Sun et al 43 . showed that SNHG12 was increased in oxidized low‐density lipoprotein‐treated vascular smooth muscle cells (VSMCs) and promoted the proliferation and migration of VSMCs, indicating SNHG12 is also involved in the atherosclerosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, miR-199a-5p might play a key role in muscle aging. In addition, some researchers have observed that the overexpression of miR-199a-5p can inhibit the proliferation and migration of vascular smooth muscle cells, which can also suppress their apoptosis ( 36 ). Compared with traditional small-tailed Han sheep, Qianhua Mutton Merino is a new breed of sheep for which meat performance has been improved.…”
Section: Discussionmentioning
confidence: 99%